Sporotrichosis in the earlobe caused by placing an earing - Evelyn Zacarias; Talita Alves; Claudilson Bastos; Paulo Athanazio; Sergio Arruda (Brazilian Journal of Infectious Diseases)
A 22-year-old woman presented with an ulcer on her right earlobe 2 months ago, with inflammation and enlarged ipsilateral lymph nodes in her neck. She was treated with antibiotics without success and then was referred to an infectious disease specialist. She has a cat at home with sporotrichosis, but without direct contact with the lesion, she did not remember any scratching by the cat. She also mentioned wearing a semi-jewel earring. This is a rare and unusual case of sporotrichosis in the earlobe, probably caused by wearing an earring contaminated by the cat's fungus that was present in the home environment. The delay in diagnosis and treatment led to the worsening of the injury and loss of the earlobe.